(untitled) (Global Journal of Science Frontier Research, 2014)
Dams are common in water scarce regions for alleviating water supply problems. However, studies have established that damming has led to the disruption of flow regime, which is the driver of river and floodplain wetland ecosystems. Historical information on the river and data on the fish species was obtained from fisherman and Kyle Recreational Park, Zimbabwe. We that observed reduced stream flow beyond the dam wall has also disrupted seasonal flow, reduced river channel and negatively impacted reproduction, growth and survival of fish and riverine vegetation. This study established the impact of flow regime on sustainable conservation and development.